(untitled) (Research, Society and Development, 2021)
This study analyzed the perceptions of the professors from a faculty of the Federal University of Pará about their teacher training and pedagogical practice in the perspective of Inclusive Education. 18 professors were interviewed, being one professor from Spanish Language, three from French Language, two from German Language and 11 from English Language. An exploratory and descriptive research with qualitative and quantitative data was adopted. As research instruments, a sociodemographic questionnaire and a questionnaire with pre-defined questions were applied through Google Forms. The statements were grouped into the following dimensions of analysis: a) Perception about teacher training; b) Perception about the importance of inclusion disciplines in the undergraduate curricula; c) Perception about experiences with students with disabilities; and d) Perception about the role of UFPA in supporting teachers. The results revealed that the majority of the professors did not have initial or continuing education or training to deal with students with disabilities in the classroom, but these participants stated that they were motivated and willing to improve their knowledge on the subject. The courses offered by the university are not enough to guarantee continuing education, as problems of communication or lack of motivation on the part of some professors were found. It was concluded that the professors who work at Faculty of Modern Foreign Letters are aware of their difficulties in relation to their pedagogical practice, of the importance of inclusion and the need for inclusive affirmative policies.